Integrating Teaching at the Right Level with Problem-Based Learning to Enhance Mathematics Learning Outcomes - Sukmawati, Dewi; Ayu Made Ratna Dewi, Ida; Hayati, Laila (AlphaMath : Journal of Mathematics Education, 2025)
This study aims to enhance students' mathematics learning outcomes at SMAN 3 Mataram by implementing the Teaching at the Right Level (TaRL) approach integrated with the Problem-Based Learning (PBL) model. Conducted as classroom action research, the study spans three cycles, each comprising four stages: planning, implementation, observation, and reflection. The subjects were 35 students from class X-1 at SMAN 3 Mataram during the second semester of the 2023/2024 academic year. Research instruments included observation sheets for lesson design implementation, written tests, and student reflection questionnaires. Results indicate that integrating TaRL with PBL significantly improved mathematics learning outcomes. In Cycle I, the average score was 77.60, with a classical mastery of 68.57%, marking a 7.11% increase from the pre-cycle. Cycle II saw the average score rise to 86.91 with a classical mastery of 85.71%, a 9.31% improvement from Cycle I. By Cycle III, the average score reached 91.00 with a classical mastery of 100%, reflecting a 4.09% increase from Cycle II. These findings conclude that the TaRL approach integrated with the PBL model significantly enhances the mathematics learning outcomes of class X-1 students at SMAN 3 Mataram in the second semester of the 2023/2024 academic year.